Investigating Neurofeedback Protocols for Stress Mitigation: A Comparative Analysis of Different Stimulus Contents - Hafeez, Y. (Institute of Electrical and Electronics Engineers Inc., 2019)
The selection of stimulus contents for neurofeedback has direct implications on the efficacy of neurofeedback therapy. In particular, a suitable selection of stimulus contents facilitates the achievement of sustainability during neurofeedback sessions, which has been considered challenging during clinical practice. To further elaborate this point, this research investigates the efficacy of different neurofeedback stimulus contents (audio, video, and games) for stress mitigation. The effectiveness of the contents was measured by statistically comparing quantitative electroencephalogram (QEEG) features, such as alpha power and alpha asymmetry before and after neurofeedback sessions. In addition, the topographic maps of activities were constructed for a visual description. In this study, 29 study participants were recruited, and the EEG data were recorded during multiple neurofeedback sessions. ANOVA and post hoc testing verified the statistical significance of the results of the various stimulus contents, whereas a t-test verified the significance of stress mitigation because of neurofeedback. The results indicate that games exhibit higher effectiveness than audio and video contents for stress mitigation. In addition, the topographic analysis demonstrates the efficacy of neurofeedback training for stress mitigation. In conclusion, the effects of neurofeedback therapy could be enhanced while selecting suitable stimulus contents for neurofeedback protocols. Â© 2013 IEEE.